"Everyone has their story": Intergroup dialogue's potential to cultivate connection through the sharing of migration narratives. Issue 4 (18th September 2022) - Castro, Elena Maker; Medina, Christian; Suárez‐Orozco, Carola
Abstract: Immigrant‐origin (I‐O) youth face increasing anti‐immigrant rhetoric in the United States, including in their schools. School‐based intergroup dialogue programming may help I‐O youth and their peers build a more inclusionary culture. We qualitatively examined how I‐O youth and their peers experienced a week‐long school‐wide intergroup dialogue program that aimed to foster connection among participants at a Northeastern high school. Participants' ( N  = 159) experience in the program were analyzed using post‐program reflections. Participants were 53% female and 74% underclassmen; 59% Latinx, 14% Black, 13% multiracial, 9% White, and 5% Asian and Middle Eastern; generationally, 54% identified as second‐generation immigrants, 38% as nonimmigrant origin, and 8% as first‐generation. Participation in the program produced mixed results. For many, participation led to a greater sense of connection; youth reported that they learned about their peers, the immigrant experience, and sometimes, themselves. Connection was especially fostered among the dominant demographic groups in the school: second‐generation and Latinx youth. Learning about others was less likely to cultivate connections when participants could not relate their own experiences, and at times even made participants feel more different from their peers. Intergroup dialogue has the potential to foster connection when participants are able to relate across experiences. Practitioner Points: For many students at one high school, participation in an intergroup dialogue program fostered a sense of connection through an exploration of a shared identity of migration. Participants were able to relate across experiences and reported that they learned about their peers, the immigrant experience, and sometimes, themselves. Connection was especially fostered among the dominant demographic groups in the school: second‐generation and Latinx youth. Learning about others was less likely to cultivate connections when participants could not relate their own experiences, and at times even made participants feel more different from their peers.